A novel metal–organic framework‐derived NiSe2/ZnSe‐NC as advanced anode materials for high‐performance asymmetric supercapacitors. Issue 2 (27th May 2021) - Xu, Rui; Chi, Kai; Wu, Jihuai; Wang, Liangjie; Lin, Jianming; Wang, Shuai
Abstract: To obtain high energy density asymmetric supercapacitors, searching anode materials with large electrochemical properties remains a great challenge. Herein, a novel anode material composed of metal−organic framework‐derived NiSe2, ZnSe, and nitrogen/carbon (NiSe2 /ZnSe‐NC) composites with high specific capacity has been successfully designed and synthesized via simple hydrothermal and two‐step calcination‐thermolysis processes. Electrochemical tests on the NiSe2 /ZnSe‐NC//active carbon asymmetric supercapacitor demonstrate an outstanding energy density of 45 W·h·kg –1 at a power density of 400 W·kg –1 and only lost 5.6% of specific capacity after 5000 cyclic voltammetry cycles. In addition, after fully charged, the assembled NiSe2 /ZnSe‐NC//active carbon asymmetric supercapacitor can easily light up a series of red light‐emitting diode indicators, indicating that the NiSe2 /ZnSe‐NC is promising as efficient anode materials for fabrication of environment‐friendly and low‐cost supercapacitors. Abstract : This work has successfully fabricated the high‐performance asymmetric supercapacitor by advanced MOF‐derived NiSe2 /ZnSe‐NC as anode materials.